2022
DOI: 10.1155/2022/6195004
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Levels of CCL23 Are Associated with Poor Outcome after Resection of Biliary Tract Cancer

Abstract: Background. Surgical tumor resection is the only potentially curative treatment option for patients with biliary tract cancer (BTC). However, 5-year survival rates are still below 50% mainly due to tumor recurrence. The preoperative identification of ideal surgical candidates has remained a major challenge and easily accessible algorithms including parameters of the individual tumor biology are missing. Chemokine (C-C motif) ligand 23 (CCl23) has been associated with tumor progression in hepatocellular carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For CXCL2, a median value of 301.44 (217.6–422.3) pg/mL is reported in healthy controls, whereas serum CXCL5 values ranged from 98.7 and up to ∼3000 pg/mL 41–43 . Similarly, a recent study reported a CCL23 median value of 266.6 (32.1–652.5) pg/mL in healthy controls 44 . However, in these studies, the healthy controls include both males and females.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For CXCL2, a median value of 301.44 (217.6–422.3) pg/mL is reported in healthy controls, whereas serum CXCL5 values ranged from 98.7 and up to ∼3000 pg/mL 41–43 . Similarly, a recent study reported a CCL23 median value of 266.6 (32.1–652.5) pg/mL in healthy controls 44 . However, in these studies, the healthy controls include both males and females.…”
Section: Discussionmentioning
confidence: 93%
“…[41][42][43] Similarly, a recent study reported a CCL23 median value of 266.6 (32.1-652.5) pg/mL in healthy controls. 44 However, in these studies, the healthy controls include both males and females. It is worth pointing out that these values can vary widely among different laboratories with different testing methods.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, high breast cancer tissue CCL8 mRNA tissue levels have been reported to increase in breast cancers compared to adjacent healthy tissues and to be associated with worse RFS [32,34]. In biliary tract cancers, elevated serum CCL23 predicted a dismal prognosis [35], and PEA-measured high plasma CCL28 levels implied worse survival in epithelial ovarian cancers [36]. Again, CCL28 levels in tumor tissue have a favorable prognostic role in luminal breast cancer but are associated with a worse prognosis in TNBC [37].…”
Section: Discussionmentioning
confidence: 99%
“…CCL23, also known as macrophage inflammatory protein 3 (MIP-3), is secreted by different immune cell types, including eosinophils, neutrophils, and monocytes [ 180 ]. Through the interaction with its ligand CCR1, this chemokine has a chemotactic effect on monocytes/macrophages, dendritic cells, lymphocytes, and ECs, and it is also able to promote angiogenesis [ 180 ]. Serum levels of CCL23 were found to be higher in SSc patients with respect to healthy individuals, and to associate with disease activity and shorter disease duration [ 181 ].…”
Section: Cytokinesmentioning
confidence: 99%